2014
DOI: 10.1039/c4rp00041b
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual integration of covalent bond models by Algerian students

Abstract: The concept of covalent bonding is characterized by an interconnected knowledge framework based on Lewis and quantum models of atoms and molecules. Several research studies have shown that students at all levels of chemistry learning find the quantum model to be one of the most difficult subjects to understand. We have tried in this paper to analyze the extent to which Algerian students, at the end of their training, have integrated the covalent bonding theories based on the quantum model of atom theory and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…A smaller fraction of studies investigated the ways that students reason with and about advanced models of bonding, such as molecular orbital theory and valence bond theory. 32,33 Moreover, we observed that over one-third of the alternative conceptions reported here have been previously reported in the 2006 review by U ̈nal et al 60 This observation suggests that we may be reaching saturation for the emergence of new themes within alternative conception-driven work, particularly in the context of students' ideas about covalent and ionic bonding at the high school and general chemistry level. Far fewer studies addressed students' ideas about advanced bonding models such as molecular orbital theory, and thus further research in the context of upper division courses such as inorganic and physical chemistry may support our understanding of how students' thinking about bonding evolves.…”
Section: Knowledge Of Studentssupporting
confidence: 63%
See 2 more Smart Citations
“…A smaller fraction of studies investigated the ways that students reason with and about advanced models of bonding, such as molecular orbital theory and valence bond theory. 32,33 Moreover, we observed that over one-third of the alternative conceptions reported here have been previously reported in the 2006 review by U ̈nal et al 60 This observation suggests that we may be reaching saturation for the emergence of new themes within alternative conception-driven work, particularly in the context of students' ideas about covalent and ionic bonding at the high school and general chemistry level. Far fewer studies addressed students' ideas about advanced bonding models such as molecular orbital theory, and thus further research in the context of upper division courses such as inorganic and physical chemistry may support our understanding of how students' thinking about bonding evolves.…”
Section: Knowledge Of Studentssupporting
confidence: 63%
“…Table 7 details alternative conceptions related to the enduring understanding "A theoretical construct that describes chemical bonding utilizes the construction of molecular orbitals for the bond based on overlap of atomic orbitals on the constituent atoms." 53 We found one set of authors who had explored undergraduate students' ideas about molecular orbital theory related concepts including atomic orbitals and hybridization 32,33 The authors documented several non-normative conceptions about hybridization of atomic orbitals, such as the idea that the orbitals resulting from hybridization are not equivalent, and that atomic orbitals remain unchanged following hybridization. 32 They noted that undergraduate students' conceptions of hybridization often involved redistribution, transfer, and excitation of electrons across the atomic orbitals of different atoms (in contrast to hybridization of a single atom's atomic orbitals).…”
Section: Incorrect Identification Of Bonds As Coordinate Covalentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the context of chemical bonding, metallic bonding is commonly referred to as a sea of electrons , which is far from self-explanatory and could explain the variety of non-normative mental models observed in the literature. Likewise, there is a need for clarity for common phrases used to describe other types of bonds such ionic bonds ( electron transfer ) and covalent bonds ( electron sharing) , with Taber asserting that electron sharing is a metaphor that “... stands for how an electron pair can bind two atomic cores through the electrical interactions between positive and negative electrical charges or implies that the shared electrons are understood to be placed in a bonding molecular orbital conceptualised as being formed by the overlap of atomic orbitals [emphasis in original],” (p 396). As before, abbreviated “memoizable” phrases are useful as long as the larger knowledge structure is explicit, with research on bonding indicating that is likely not the case, in part due to the overemphasis of heuristics such as the octet rule, ,, which may support unproductive conceptualizations such as a molecular (instead of lattice) view of ionic bonding. ,,, …”
Section: Conclusion and Implicationsmentioning
confidence: 99%
“…All of the atoms in the network structure of trans‐PA, on the other hand, have partially filled π ‐bonded p‐orbitals. [ 31 ]…”
Section: Conductive Polymersmentioning
confidence: 99%